Unsteady Heat Transfer Analysis on The MHD Flow of A Second Grade Fluid in A Channel with Porous Medium - Ridha, Safa; Abdulhadi, Ahmed (Iraqi Journal of Science, 2023)
The aim of this paper is to analyzed unsteady heat transfer for magnetohydrodynamic (MHD) flow of a second grade fluid in a channel with porous medium. The equations which was used to describe the flow are the momentum and energy, these equations were written to get thier non dimentional form. Homotopy analysis method (HAM) is employed to obtain a semi-analytical solutions for velocity and heat transfer fields. The effect of each dimensionless parameter upon the velocity and temperature distributions is analyzed and shown graphically by using MATHEMATICA package.